2005
DOI: 10.1136/pgmj.2005.033076
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in mechanically ventilated patients

Abstract: Objectives: There are scarce data from India validating scoring systems used to predict outcome in patients requiring mechanical ventilation. This study prospectively compared the organ system failure (OSF), the acute physiology and chronic health evaluation (APACHE) II, and the APACHE III, scores on patients requiring mechanical ventilation in the medical intensive care unit, to predict outcome. Methods: 200 consecutive patients requiring mechanical ventilation in a medical intensive care unit were recruited.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
30
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 22 publications
4
30
3
Order By: Relevance
“…Age was reported to be significantly and inversely associated with survival in dogs and cats undergoing PPV, such that each 1‐year increase in age, led to a 10% decrease in the survival odds (Hopper et al ). Similarly, in a study using the acute physiological and chronic health (APACH II) scoring system in ventilated humans, significantly higher survival rates were noted in younger (<34 years) PPV‐treated patients compared with older (>43 years) ones (Sudarsanam et al ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Age was reported to be significantly and inversely associated with survival in dogs and cats undergoing PPV, such that each 1‐year increase in age, led to a 10% decrease in the survival odds (Hopper et al ). Similarly, in a study using the acute physiological and chronic health (APACH II) scoring system in ventilated humans, significantly higher survival rates were noted in younger (<34 years) PPV‐treated patients compared with older (>43 years) ones (Sudarsanam et al ).…”
Section: Discussionmentioning
confidence: 90%
“…The reported association between the duration of PPV and survival in humans is inconsistent. One study recorded a positive association between the two (Sudarsanam et al ), while others noted a negative one, partly due to prolonged PPV‐associated complications, especially VAP and airway trauma (Boles et al , Zanella et al ). In this study, there was no difference in the overall median duration of PPV between the outcome groups, in agreement with a previous veterinary report (Hopper et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Sudarsanam and co-workers [11] reported that one of the predictors of mortality in mechanically ventilated patients was the use of ionotropes. The reason for this finding may be due to the interplay which exists between the cardiovascular and respiratory systems.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported earlier by Hsu, Wann et al 20 in patients with respiratory failure due to various causes in a medical ICU and by Senef.et al 21 who found (A-a) DO2 to be more strongly associated with 180 day mortality rates (22% of explanatory power) than in-hospital mortality rates (4% of explanatory power) in patients admitted to ICU with acute exacerbation of COPD. In contrast, Sudarshanam et al 22 found (A-a) DO2 to be significantly associated with mortality on univariate analysis but was not an independent predictor on logistic regression analysis in a study comprising patients with respiratory failure due to all causes including COPD.…”
Section: Discussionmentioning
confidence: 79%